2007
DOI: 10.1053/j.gastro.2006.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Novel Resequencing Chip Customized to Diagnose Mutations in Patients With Inherited Syndromes of Intrahepatic Cholestasis

Abstract: Background and Aims-Inherited syndromes of intrahepatic cholestasis commonly result from mutations in the genes SERPINA1 (α1-antitrypsin deficiency), JAG1 (Alagille syndrome), ATP8B1 (Progressive Familial Intrahepatic Cholestasis type 1/PFIC1), ABCB11 (PFIC2), and ABCB4 (PFIC3). However, the large gene sizes and lack of mutational hotspots make it difficult to survey for disease-causing mutations in clinical practice. Here, we aimed to develop a technological tool that reads out the nucleotide sequence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 50 publications
4
66
1
10
Order By: Relevance
“…7,8,12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][57][58][59] This study showed that some ABCB11 missense mutations were associated with splicing defects, most caused protein processing defects, and the two functionally analyzed showed a reduction in taurocholate transport. Additionally, the ability to modulate splicing and protein processing defects was examined; some mutations were amenable to such treatments.…”
Section: Discussionmentioning
confidence: 75%
“…7,8,12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][57][58][59] This study showed that some ABCB11 missense mutations were associated with splicing defects, most caused protein processing defects, and the two functionally analyzed showed a reduction in taurocholate transport. Additionally, the ability to modulate splicing and protein processing defects was examined; some mutations were amenable to such treatments.…”
Section: Discussionmentioning
confidence: 75%
“…High-density oligonucleotide microarrays offer the opportunity to conduct both tests on a single analytical platform. Although single-nucleotide polymorphism arrays have been used extensively, little is known about the sensitivity of mutation detection with ABR (4,6 ). Our data suggest that the HCM1 array is an effective alternative to conventional capillary sequencing.…”
Section: Discussionmentioning
confidence: 80%
“…Although its first application was in SNP discovery and genotyping, recent reports have evaluated resequencing arrays as a means of finding human disease-causing mutations in hypogonadotrophic hypogonadism, 22 congenital myasthenia, 22 retinitis pigmentosum, 27 lung cancer, 28 and intrahepatic cholestasis. 29 All of these studies achieved overall call rates exceeding 90% using methods based on adaptive background genotype calling scheme algorithms of Cutler et al, 20 which …”
Section: Genementioning
confidence: 99%